Transformerless UPFC Using Multilevel Inverter (International Journal of Engineering and Computer Science, 2017)
This paper proposes transformer-less Unified Power Flow Controller (UPFC) which can be able to control the parameters of the transmission line. It incorporates back to back inverter that requires large transformers for power flow injection. The transformers are somewhat bulky, very costly and introduce high losses due to magnetic properties of the material used for the erection of core. To conquer this difficulty, a totally transformer-less UPFC is proposed in this work. The proposed controller will reduce the cost and space when compared to the traditional UPFC. A multilevel configuration technique will be used to decrease the total harmonic content. The proposed configuration requires a separate dc source for every level. To reduce the switch count and to eliminate separate dc sources, this multilevel configuration can be further modified. This paper focuses on the performance of transformer-less UPFC involving Fundamental Frequency Modulation (FFM) for reducing the Total Harmonic Distortion (THD) and increasing the efficiency. The proposed UPFC is simulated as a result of using MATLAB Simulink.